2021
DOI: 10.1051/matecconf/202134603028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ratio of Heat Exchanging Tube Finning on Heat Exchanger Efficiency

Abstract: For the purpose of thermal and hydraulic and aerodynamic testing of the heat exchanger tube bundles, various full-scale tube specimens with different finning ratio have been proposed. Formulas that allow to evaluate the effect of the ratio of heat exchanging tube finning on the heat exchanger efficiency are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The fin discontinuity in front of the tube causes the smallest reduction in the heat transfer rate in comparison with the ideal tube-fin contact, especially for thin slits. In 2021, Khizhov et al [16] carried out thermal, hydraulic, and pneumatic tests on the tube bundle of the heat exchanger and presented full-size tube samples with different fin ratios. The formula for calculating the effect of fin ratio on heat exchanger efficiency was given.…”
Section: Introductionmentioning
confidence: 99%
“…The fin discontinuity in front of the tube causes the smallest reduction in the heat transfer rate in comparison with the ideal tube-fin contact, especially for thin slits. In 2021, Khizhov et al [16] carried out thermal, hydraulic, and pneumatic tests on the tube bundle of the heat exchanger and presented full-size tube samples with different fin ratios. The formula for calculating the effect of fin ratio on heat exchanger efficiency was given.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that whether the surface of the heat exchange tube was magnetic or not had a significant effect on its fouling resistance. Lu et al [27] investigated particle deposition at different flow states. The results showed that for particles with small particle sizes (dp < 20 µm), the thermal network deposition led to a sharp increase in the particle deposition rate, but for particles with larger particle sizes (dp > 20 µm), it remained constant.…”
Section: Introductionmentioning
confidence: 99%